Thiosemicarbazonecopper/Halido Systems: Structure and DFT Analysis of the Magnetic Coupling - Alondra Jiménez-Pérez; Sara Marcos-Gómez; Gotzon Madariaga; Manuel Zapico; Pablo Vitoria; Javier Tercero; M. Begoña Torres; Luis Lezama; José Vicente Cuevas; Iñigo Etxebarria; Javier García-Tojal (Inorganics, 2023)
Experimental magnetic studies performed on the [{CuLX}2] system (HL = pyridine-2-carbaldehyde thiosemicarbazone, X = Cl−, Br−, I−) point to the larger electronegativity in X, the lower magnitude of the antiferromagnetic interactions. In order to confirm this and other trends observed and to dip into them, computational studies on the [{CuLX}2] (X = Cl− (1), I− (2)) compounds are here reported. The chemical and structural comparisons have been extended to the compounds obtained in acid medium. In this regard, chlorido ligands yield the [Cu(HL)Cl2]∙H2O (3) complex, whose crystal structure shows that thiosemicarbazone links as a tridentate chelate ligand to square pyramidal Cu(II) ions. On the other hand, iodido ligands provoke the formation of the [{Cu(H2L)I2}2] (4) derivative, which contains pyridine-protonated cationic H2L+ as a S-donor monodentate ligand bonded to Cu(I) ions. Crystallographic, infrared and electron paramagnetic resonance spectroscopic results are discussed. Computational calculations predict a greater stability for the chlorido species, containing both the neutral (HL) and anionic (L−) ligand. The theoretical magnetic studies considering isolated dimeric entities reproduce the sign and magnitude of the antiferromagnetism in 1, but no good agreement is found for compound 2. The sensitivity to the basis set and the presence of interdimer magnetic interactions are debated.